The Fact-Finding Security Examination in NFC-enabled Mobile Payment System - Pinki Prakash Vishwakarma; Amiya Kumar Tripathy; Srikanth Vemuru (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Contactless payments devised for NFC technology are gaining popularity. Howbeit, with NFC technology permeating concerns about arising security threats and risks to lessen mobile payments is vital. The security analysis of NFC-enabled mobile payment system is precariously imperative due to its widespread ratification. In mobile payments security is a prevalent concern by virtue of the financial value at stave. This paper assays the security of NFC based mobile payment system. It discusses the security requirements, threats and attacks that could occur in mobile payment system and the countermeasures to be taken to secure pursuance suitability.